Phytase and phosphate-solubilizing Bacteria addition improves P availability and uptake by maize in low-phosphorus red soil - Long Zhou; Litao Zhu; Faming Zhang (PLoS ONE, 2026)
This study investigated the effects of phytase (PHY) and phosphate-solubilizing Bacillus (PSB) isolates on maize growth and phosphorus (P) acquisition in low-P red soil, under conditions with or without organic P application. A pot experiment demonstrated that the combined application of organic P with exogenous PHY and PSB significantly enhanced maize agronomic traits, root morphology, rhizosphere properties, and P mobilization. Compared to the P-free control, organic P application alone increased plant height, stem diameter, dry matter, and P uptake by 9.9%, 5.4%, 23.2%, and 34.6%, root surface area, volume, and branching increased by 39.7%, 26.7%, and 44.7%, while average root diameter decreased by 19.5%, respectively. Exogenous phytase treatment was more effective than bacterial adding in enhancing P activation and uptake, increasing maize P absorption by 55.4% and 47.3% with and without sodium phytate, respectively. Redundancy analysis indicated positive correlations between root traits (root tips, surface area, volume) and P uptake, and between Olsen-P, resin-P, NaHCO₃-Pi, and enzyme activities. The results suggest that combining organic P with exogenous phytase effectively mobilizes native soil P pools, improves maize growth, and increases P use efficiency, offering a sustainable strategy for P management in low-P red soils.